Archaismus - Schubert, Katrin (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik.)

Do Shy Children Behave Differently than Non-shy Children in a Long-term Child-robot Interaction? - Tolksdorf, Nils Frederik; Viertel, Fanziska; Rohlfing, Katharina J. (Companion of the 2020 ACM/IEEE International Conference on Human-Robot Interaction)

Parents’ Views on Using Social Robots for Language Learning - Tolksdorf, Nils Frederik; Rohlfing, Katharina J. (2020 29th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN))

Children’s Narrative Elaboration After Reading a Storybook Versus Viewing a Video - Crawshaw, Camilla E.; Kern, Friederike; Mertens, Ulrich; Rohlfing, Katharina (Frontiers in Psychology)

The role of caregivers in keeping a child-robot interaction going. - Rohlfing, Katharina; Grimminger, Angela; Wrede, Britta (International perspectives on digital media and early literacy: The impact of digital devices on learning, language acquisition and social interaction.)

Ethical Considerations of Applying Robots in Kindergarten Settings: Towards an Approach from a Macroperspective - Tolksdorf, Nils F.; Siebert, Scarlet; Zorn, Isabel; Horwath, Ilona; Rohlfing, Katharina J. (International Journal of Social Robotics)
In child–robot interaction (cHRI) research, many studies pursue the goal to develop interactive systems that can be applied in everyday settings. For early education, increasingly, the setting of a kindergarten is targeted. However, when cHRI and research are brought into a kindergarten, a range of ethical and related procedural aspects have to be considered and dealt with.While ethical models elaborated within other human–robot interaction settings, e.g., assisted living contexts, can provide some important indicators for relevant issues, we argue that it is important to start developing a systematic approach to identify and tackle those ethical issues which rise with cHRI in kindergarten settings on a more global level and address the impact of the technology from a macroperspective beyond the effects on the individual. Based on our experience in conducting studies with children in general and pedagogical considerations on the role of the institution of kindergarten in specific, in this paper,we enfold some relevant aspects that have barely been addressed in an explicit way in current cHRI research. Four areas are analyzed and key ethical issues are identified in each area: (1) the institutional setting of a kindergarten, (2) children as a vulnerable group, (3) the caregivers’ role, and (4) pedagogical concepts. With our considerations, we aim at (i) broadening the methodology of the current studies within the area of cHRI, (ii) revalidate it based on our comprehensive empirical experience with research in kindergarten settings, both laboratory and real-world contexts, and (iii) provide a framework for the development of a more systematic approach to address the ethical issues in cHRI research within kindergarten settings.
Keywords: Robot ethics · Kindergarten settings · Child–robot interaction · Early childhood education

Wie meinst du das? - Begriffserwerb im Religionsunterricht - Kohlmeyer, Theresa; Reis, Oliver; Viertel, Franziska; Rohlfing, Katharina (Theo Web)

International Perspectives on Digital Media and Early Literacy

Ethical considerations of applying robots in kindergarten settings: Towards an approach from a macroperspective. - Tolksdorf, Nils Frederik; Siebert, Scarlet; Zorn, Isabel; Horwarth, Ilona; Rohlfing, Katharina (International Journal of Social Robotics)

Integrated Communication System: Gesture and language acquisition in typically developing children and children with LD and DLD - Lüke, Carina; Ritterfeld, Ute; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf (Frontiers in Psychology 11)

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin

Digitales Lesen

Lernaufgaben im inklusiven Sprachunterricht. - Topalović, Elvira; Uhl, Benjamin (Inklusion und Kooperation. Fördermagazin Grundschule)

Digitales Lesen: Empirische Evidenzen für den Deutschunterricht - Topalović, Elvira (Der Deutschunterricht)

Sprachliches und literarisches Lernen mit Texten in einfacher Sprache. Deutschdidaktische Kontroversen am Beispiel des Romans „Tschick“. - Topalović, Elvira; Diederichs, Lara (Sprache als Herausforderung – Literatur als Ziel. Kinder- und jugendliterarische Texte und Medien als Ressource für sprachsensibles Lernen.)

Wortgruppen entdecken. - Lang, Susanne; Topalović, Elvira (Praxis Deutsch)

Die Wortgruppe als Rechtschreib- und Lesestrategie. - Topalović, Elvira; Lang, Susanne (In: Lernen lernen. Fördermagazin Grundschule)

Bilder verstehen – Bilder gebrauchen (Modul 4) - Blachut, Alisa (Deutsch lernen: Sprechen – Zuhören – Lesen – Schreiben. DaM – DaZ – DaF. Arbeitsheft 2)

Generationelle und gesellschaftliche Differenzen im wiedervereinigten Deutschland - "Der neunzigste Geburtstag. Ein ländliches Idyll" von Günter de Bruyn in postkolonialer Lesart. - Müller, Inez